Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.stem.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The Zika Virus Capsid Disrupts Corticogenesis by Suppressing Dicer Activity and miRNA Biogenesis

Abstract: Highlights d Defining the ZIKV-host interactome in NSCs identifies a capsid-Dicer interaction d Capsid from ZIKV but not other flaviviruses binds Dicer and blocks its activity d ZIKV capsid dampens global miRNA production in NSCs by targeting Dicer d ZIKV capsid is necessary and sufficient to drive neurodevelopmental defects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 63 publications
1
74
0
1
Order By: Relevance
“…ZIKV strain SPH2015 and according ZIKV-H41R mutant virus were separately rescued from the ZIKV infection clone as described previously ( Zeng et al., 2020 ). Vero cells were cultured in DMEM with 10% FBS and 4 mM glutamine.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…ZIKV strain SPH2015 and according ZIKV-H41R mutant virus were separately rescued from the ZIKV infection clone as described previously ( Zeng et al., 2020 ). Vero cells were cultured in DMEM with 10% FBS and 4 mM glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…NSCs were plated on poly-L-Ornithine (10 µg/ml) coated plates when adherent culture was needed. ZIKV WT capsid and H41R capsid were cloned into lentivirus pCDH-cmv-mcs-ef1-puro vector as described previously ( Zeng et al., 2020 ). Lentiviruses were generated by co-transfection of pCDH-vector, pCDH-Flag-capsid WT or pCDH-Flag-capsid H41R with three packaging plasmids into HEK293T cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant difference between viral strains of Asian and African lineages was shown for the interaction between C protein and the NMD pathway (Fontaine et al, 2018). Recently, a study also reported that C protein specifically binds and inhibits Dicer to limit host miRNA biogenesis in neural stem cells (NSCs), resulting in neurodevelopmental defects and virus immune evasion (Zeng et al, 2020).…”
Section: Capsid Proteinmentioning
confidence: 99%